Education on the Fulfillment of Balanced Nutrition and My Plate Contents for Students of SMPN 7 Kendari - Lisnawaty; Rizki Eka Sakti Octaviani; Yusuf Sabilu (CV. Literasi Indonesia, 2021)
To achieve optimal nutritional status, a country needs guidelines for balanced nutrition. One of the visualizations of balanced nutrition messages is 'My Dinner Plate' which shows the serving of food and drinks at each meal. The purpose of this service program is to provide information and knowledge about the fulfillment of balanced nutrition and the contents of my plate to adolescents, especially students of SMPN 7 Kendari. The target of this program is students of SMPN 7 Kendari, especially those in Class VII. This program consists of counseling through power points and videos on general guidelines for balanced nutrition and the contents of my plate, discussions and questions and answers, and distributing pre-post questionnaires. The results of this activity were as many as 44 students as respondents consisting of 31.8% male students and 68.2% female students. The mean knowledge of the sample before the extension was 4.50 with a standard deviation of 1.535. Meanwhile, after counseling, the average sample knowledge increased to 7.64 with a standard deviation of 1.293. The results of statistical tests showed that the value of p = 0.000 where the value of p = <0.05, it can be concluded that there is an effect of counseling on the fulfillment of balanced nutrition and the contents of my plate. There needs to be further counseling and mentoring activities so that the knowledge gained can be applied in daily life.